Spectral flow for pair compatible equipartitions. Issue 1 (17th January 2022) - Helffer, Bernard; Sundqvist, Mikael Persson
Abstract: We show that a recent spectral flow approach proposed by Berkolaiko–Cox–Marzuola for analyzing the nodal deficiency of the nodal partition associated to an eigenfunction can be extended to more general partitions. To be more precise, we work with spectral equipartitions that satisfy a pair compatible condition. Nodal partitions and spectral minimal partitions are examples of such partitions. Along the way, we discuss different approaches to the Dirichlet-to-Neumann operators: via Aharonov–Bohm operators, via a double covering argument, and via a slitting of the domain.